2013
DOI: 10.1603/en13143
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pheromone Timed Insecticide Applications Integrated With Mating Disruption or Mass Trapping Against <I>Ostrinia furnacalis</I> (Lepidoptera: Pyralidae) in Sweet Corn

Abstract: Mating disruption and mass trapping of Ostrinia furnacalis (Génuéé), often called the Asian corn borer, were incorporated with insecticides to reduce pesticide use. Pesticides alone are often ineffective owing to problems in timing applications before the larvae enter the protection of corn stalks. In addition, overuse of insecticides has caused environmental contamination and concerns about consumer health. In 2010, 15 insecticides were compared with mating disruption or mass trapping at various dispenser (di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
1
11
1
Order By: Relevance
“…Sex pheromones are an ideal component of integrated pest management programs (Liu and Zhang 2006, Chen and Li 2011, Chen and Klein 2012, Chen et al 2013a, and are a suggested tactic for moth mating disruption when the proper number of dispensers are placed in Þelds , Witzgall et al 2008. Information here correlates positively with previous research.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Sex pheromones are an ideal component of integrated pest management programs (Liu and Zhang 2006, Chen and Li 2011, Chen and Klein 2012, Chen et al 2013a, and are a suggested tactic for moth mating disruption when the proper number of dispensers are placed in Þelds , Witzgall et al 2008. Information here correlates positively with previous research.…”
Section: Discussionsupporting
confidence: 58%
“…This was accomplished by putting 18 dispensers of each type of lure and then removing 3 of them for residue assessment every 5 d from the Þfth to thirtieth day after the exposure. The details on identiÞcation of components were similar to those by Chen et al (2013a). The exceptions were that dispensers were stored at Ϫ22ЊC, and ethyl phenethyl was used as the internal standard for phenethyl propionate, acetone for (R, Z)-5-(I-decenyl) dihydro-2( 3 H)-furanone, phenol for eugenol, and butyl acetate for geraniol.…”
Section: Methodsmentioning
confidence: 99%
“…Population Dynamics. An automatic water-supplemented pheromone trap (Chen and Klein 2012;Chen et al , 2013) was used to assess male moth activity as a trigger for mass trapping and mating disruption in the three years, to compare moth populations between 2011, 2012, and 2013, and to evaluate the possible carry-over effect of 2011 applications. Nine traps were divided into three groups and placed diagonally in the control plots from 1 May to 30 October during the three years.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, there is an urgent need to develop the environmentally friendly methods to control this pest. Among these known modes, such as chemical, biological, or physical pest control, it is an ideal way to control ACB pests by using the sex pheromone mass trapping or mating disruption, because it has the characteristics of being of low cost, environmentally friendly, of low dosage, of strong selectivity, and of high sensitivity [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%